Applications of superparamagnetic nanoparticles for the separation and recovery of PGM metals from acidic wastewater solutions - Khutlane, Joyce Tsepiso (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.